GIS-based earthquake disaster management system for seismic risk assessment: a case study of Sabah and Pahang, Malaysia - Sauti, Noor Suhaiza (2022)
Earthquake disaster management in Malaysia is still at the initial stages and faces multiple challenges. There is a dearth research on, and tools for, seismic risk assessment when estimating the impact of earthquakes for specific areas. Furthermore, the absence of a central authority to integrate earthquake disaster management and lack of coordination among organizations has caused crucial data related to the earthquakes to be managed separately and in different formats. Therefore, this research aim is to develop a GIS-based earthquake management system for seismic risk assessment that involves the development and verification of the seismic vulnerability index for Malaysia; the development of a GIS-based earthquake management system database for risk management planning; and an evaluation of the proposed seismic vulnerability and risk assessment modeling system. The methodology specifically relies on the development of a set of vulnerability index indicators using multivariate data analysis to identify the local characteristics that contribute to the vulnerability and risk of inhabitants at the district scale; and the development of GIS-based system with a modeling application to generate and map the spatial distributions of seismic vulnerability and risk. The study revealed the highest levels of seismic risk were concentrated in the centre-west of the Pahang region, namely the Bentong district, whereas in Sabah the riskiest areas encompassed the district of Lahad Datu, Sandakan, Semporna, Tawau and Kunak. Evaluation of risk assessment modeling systems through the integration of verification and validation processes demonstrates a reliable and robust modeling system to perform vulnerability and risk assessment. Finally, the contribution of this study offers an alternative methodology for developed countries, which often face the lack of comprehensive and readily available data for vulnerability assessment. The weighting scheme method has been extensively used in several disciplines, particularly the field of climate change and has yet to be applied for calculating weights for seismic vulnerability and risk indicators.